Atypical pityriasis rosea presenting with a herald patch lesion on the healed site of herpes zoster: Wolf's isotopic response - Üstüner, Pelin; Balevi, Ali; Özdemir, Mustafa; Türkmen, İlknur (John Libbey Eurotext Ltd, 2016)
A 37-year-old man presented with a one-month history of pruritic skin lesions on his trunk, back and legs. The lesions first appeared in his right lumbar area, resembling a medallion, becoming widespread over two weeks with newer, smaller lesions over his trunk and right leg. His medical history and systemic examination were unremarkable. One year previously he had been diagnosed with herpes zoster (HZ) and treated with valacyclovir and gabapentin for HZ and post-herpetic neuralgia that completely resolved after six months.
WOS: 000374206200023
PubMed ID: 26678150
Keywords: Acanthosis; Dermatome; Electron Microscopy; Pityriasis Rosea